Measurement of electron trapping in the Cornell Electron Storage Ring - M. G. Billing; J. Conway; E. E. Cowan; J. A. Crittenden; W. Hartung; J. Lanzoni; Y. Li; C. S. Shill; J. P. Sikora; K. G. Sonnad (Physical Review Special Topics. Accelerators and Beams, 2015)
The buildup of low-energy electrons has been shown to affect the performance of a wide variety of particle accelerators. Of particular concern is the persistence of the cloud between beam bunch passages, which can impose limitations on the stability of operation at high beam current. We have obtained measurements of long-lived electron clouds trapped in the field of a quadrupole magnet in a positron storage ring, with lifetimes much longer than the revolution period. Based on modeling, we estimate that about 7% of the electrons in the cloud generated by a 20-bunch train of 5.3 GeV positrons with 16-ns spacing and 1.3×10^{11} population survive longer than 2.3  μs in a quadrupole field of gradient 7.4  T/m. We have observed a nonmonotonic dependence of the trapping effect on the bunch spacing. The effect of a witness bunch on the measured signal provides direct evidence for the existence of trapped electrons. The witness bunch is also observed to clear the cloud, demonstrating its effectiveness as a mitigation technique.